2019
DOI: 10.4103/ijo.ijo_1465_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plusoptix S12R photoscreener with cycloplegic retinoscopy and autorefraction in pediatric age group

Abstract: Purpose:To compare refractive measurements of noncycloplegic photoscreener Plusoptix S12R with cycloplegic retinoscopy, noncycloplegic autorefractor, and cycloplegic autorefractor in children.Methods:The study population (200 eyes of 100 children) was divided into two groups: Group 1 (age 3–7 years) and Group 2 (age 8–15 years). In Group 1, Plusoptix was compared with cycloplegic retinoscopy. In Group 2, Plusoptix was compared with cycloplegic retinoscopy and autorefraction. The second group was made because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Saini et al also reported an increase of 0.94D and 0.93D in the sphere and SE, respectively, in children (3–7 years). They found a cylinder difference of 0.02D after cycloplegia with an autorefractor [ 40 ]. Payerols et al found an SE increase of 1.02D after cycloplegia in a Nidek ARK-530A autorefractor in children older than 3 years, and of 3.16D under cycloplegia in a portable Retinomax autorefrator in children younger than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Saini et al also reported an increase of 0.94D and 0.93D in the sphere and SE, respectively, in children (3–7 years). They found a cylinder difference of 0.02D after cycloplegia with an autorefractor [ 40 ]. Payerols et al found an SE increase of 1.02D after cycloplegia in a Nidek ARK-530A autorefractor in children older than 3 years, and of 3.16D under cycloplegia in a portable Retinomax autorefrator in children younger than 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…(0.94, 0, 92, 0.93). [ 4 11 20 25 ] Good correlation was reported between Plusoptix screener and cycloplegic refraction by Payerols et al . The authors highlighted the need for large scale population-based studies to corroborate the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Patient accommodation can lead to more myopic values when using the RTX without cycloplegia, and more hyperopic values with the PO may be related to the fact that measurements are taken from a distance of 1 meter, eliminating the factor of accommodation. The PO can detect strabismus, refractive errors, and even media opacity, potentially eliminating the need for a dilated fundus examination in some patients (17).…”
Section: Discussionmentioning
confidence: 99%